Handbook of Youth Suicide Prevention 2021
DOI: 10.1007/978-3-030-82465-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Suicide-Related Risk in Immigrant and Ethnic and Racial Minority Youth Through an Ecological and Developmental Context

Abstract: The US is home to the world’s largest immigrant population, with an estimated 51 million foreign-born migrants, who largely originate from the global south. A significant proportion of the US population thus experiences acculturation or psychological changes as they navigate between different cultural environments. Contemporary conceptualizations of acculturation draw on a bidimensional conceptualization that posits heritage retention and acquisition of the host culture as independent dimensions spread across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 119 publications
3
4
0
Order By: Relevance
“…Comparison of ABCD bicultural and detached profiles indicated that biculturalism was associated with more positive mental health outcomes in agreement with a wealth of previous acculturation research (10,18,19,71,72). However, these prior studies are characterized by the use of individual rating inventories that separately measure symptoms of a single disorder (e.g., depression).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Comparison of ABCD bicultural and detached profiles indicated that biculturalism was associated with more positive mental health outcomes in agreement with a wealth of previous acculturation research (10,18,19,71,72). However, these prior studies are characterized by the use of individual rating inventories that separately measure symptoms of a single disorder (e.g., depression).…”
Section: Discussionsupporting
confidence: 86%
“…Comparison of ABCD bicultural and detached profiles indicated similar demographics, with the exception of higher educational attainment among bicultural caregivers. Biculturalism was associated with positive caregiver behaviors and mental health, including increased personal strengths and decreased affective and thought problems, in agreement with a wealth of prior acculturation research (8,9,15,23,24).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Comparison of ABCD Study bicultural and detached profiles indicated that biculturalism was associated with more positive mental health outcomes, in agreement with a wealth of previous acculturation research ( 10 , 66 , 67 ). However, these prior studies are characterized by the use of individual rating inventories that separately measure symptoms of a single disorder (e.g., depression).…”
Section: Discussionsupporting
confidence: 86%